Targeted Drug Strategies for Cancer and Inflammation - Jackman, Ann L.; Leamon, Christopher P. (Springer New York : Imprint: Springer, 2011)
The discoveries highlighted in this book parallel the emergence of innovative "molecular targeted" small molecules and monoclonal antibodies, i.e. agents that target proteins within highly activated signal transduction pathways that control proliferation.  Many of the tumor-targeted strategies described within cross the boundaries between what's considered to be "molecular targeted" versus conventional systemic therapy.  However, the main theme of this volume is the folate receptor (FR), with much of the content focused on its basic biology and regulation as well as its exploitation for targeted therapy and diagnostic imaging.